1999
DOI: 10.1046/j.1525-1438.1999.09903.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18F-fluoro-deoxyglucose positron emission tomography (18F-FDG PET) in diagnosis of ovarian cancer

Abstract: We evaluated the clinical significance of 18F-FDG PET to detect malignant ovarian neoplasms and tumor spread. 40 patients (median age: 57.5 years) underwent laparotomy because of clinical suspicion of malignant ovarian tumors or recurrent disease. The results of the preoperatively performed PET were correlated with the postoperative histologic diagnosis and the intraoperatively assessed tumor spread. In 10 of 40 patients benign tumors were found, among which a tubo-ovarian abscess was the only one diagnosed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
3
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 19 publications
1
25
3
5
Order By: Relevance
“…The observed correlation between increased GLUT1 expression, increased glycolysis and an intracellular accumulation of 2-fluoro-deoxy- D -glucose (FDG) in tumor cells might represent the biological basis for 18 F-FDG positron emission tomography [24]. As the results of clinical studies show, there is, in particular, an indication in relapse diagnosis suggesting this examination technique in the case of patients with ovarian carcinoma [25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed correlation between increased GLUT1 expression, increased glycolysis and an intracellular accumulation of 2-fluoro-deoxy- D -glucose (FDG) in tumor cells might represent the biological basis for 18 F-FDG positron emission tomography [24]. As the results of clinical studies show, there is, in particular, an indication in relapse diagnosis suggesting this examination technique in the case of patients with ovarian carcinoma [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that GLUT3 is expressed selectively in several human tumors such as brain neoplasms or non-small cell lung carcinoma [22, 23]. In ovarian cancer, increased glucose uptake demonstrated by positron emission tomographic studies [24] suggests a pathophysiological role of glucose metabolism and the different GLUT isoforms [25]. Recently, first reports on GLUT1 expression in ovarian cancer have suggested this glucose transporter to be overexpressed and related to aggressive tumor biological behavior [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal marker levels often precede clinical and radiologic signs of disease recurrence. 18 F-FDG PET has been shown to be limited in the diagnosis of cancer of the ovaries (28)(29)(30)(31)(32)(33)(34)(35). Physiologic 18 F-FDG uptake observed in the ovaries of women of reproductive age even after hysterectomy is reasonably common and may be mistaken for pathologic uptake.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…La PET obtiene unas cifras de sensibilidad comparables a las de la TAC (50-90%), pero con mayor especificidad (60-80%) (Tabla I). No obstante, es incapaz de detectar la mayor parte de los tumores en estadio I y aquellos de malignidad "borderline", al correlacionarse la captación de FDG con el grado histológico 19,21 . Además, se pueden producir falsos positivos en lesiones benignas tales como endometriosis, tumores quísticos, teratomas, schwanomas, enfermedades inflamatorio-infecciosas y hemorragias del cuerpo lúteo.…”
Section: Diagnóstico Primario De Malignidadunclassified
“…Es sabido, además, que la TAC y la RM no pueden descartar implantes peritoneales de pequeño tamaño. La PET obtiene en estos casos una sensibilidad y especificidad del 50-78% y 86-95% 19,24 , respectivamente, cifras superiores a las obtenidas por las téc-nicas convencionales. Frecuentemente se escapan a la detección lesiones microscópicas o micronodulares 24,29 .…”
Section: Estadificación Tumoral Pre-terapéuticaunclassified